Deep intracerebral (basal ganglia) haematomas in fatal non-missile head injury in man. Issue 9 (September 1986) - Adams, J H; Doyle, D; Graham, D I; Lawrence, A E; McLellan, D R
Abstract : Deep intracerebral (basal ganglia) haematomas were found post mortem in 63 of 635 fatal non-missile head injuries. In patients with a basal ganglia haematoma, contusions were more severe, there was a reduced incidence of a lucid interval, and there was an increased incidence of road traffic accidents, gliding contusions and diffuse axonal injury than in patients without this type of haematoma. Intracranial haematoma is usually thought to be a secondary event, that is a complication of the original injury, but these results suggest that a deep intracerebral haematoma is a primary event. If a deep intracerebral haematoma is identified on an early CT scan it is likely that the patient has sustained severe diffuse brain damage at the time of injury. In the majority of head injuries damage to blood vessels or axons predominates. In patients with a traumatic deep intracerebral haematoma, it would appear that the deceleration/acceleration forces are such that both axons and blood vessels within the brain are damaged at the time of injury.